Deletion of Tmtc4 activates the unfolded protein response and causes postnatal hearing loss - Jiang Li; Omar Akil; Stephanie L. Rouse; Conor W. McLaughlin; Ian R. Matthews; Lawrence R. Lustig; Dylan K. Chan; Elliott H. Sherr (The Journal of Clinical Investigation, 2018)
Hearing loss is a significant public health concern, affecting over 250 million people worldwide. Both genetic and environmental etiologies are linked to hearing loss, but in many cases the underlying cellular pathophysiology is not well understood, highlighting the importance of further discovery. We found that inactivation of the gene Tmtc4 (transmembrane and tetratricopeptide repeat 4), which was broadly expressed in the mouse cochlea, caused acquired hearing loss in mice. Our data showed Tmtc4 enriched in the endoplasmic reticulum, and that it functioned by regulating Ca2+ dynamics and the unfolded protein response (UPR). Given this genetic linkage of the UPR to hearing loss, we demonstrated a direct link between the more common noise-induced hearing loss (NIHL) and the UPR. These experiments suggested a novel approach to treatment. We demonstrated that the small-molecule UPR and stress response modulator ISRIB (integrated stress response inhibitor), which activates eIF2B, prevented NIHL in a mouse model. Moreover, in an inverse genetic complementation approach, we demonstrated that mice with homozygous inactivation of both Tmtc4 and Chop had less hearing loss than knockout of Tmtc4 alone. This study implicated a novel mechanism for hearing impairment, highlighting a potential treatment approach for a broad range of human hearing loss disorders.